2022
DOI: 10.16920/jeet/2022/v35is1/22018
|View full text |Cite
|
Sign up to set email alerts
|

Enriching and Energizing the Virtual Classroom using Breakout Sessions: A better experience of Active Learning during Covid- 19 Pandemic.

Abstract: over the World. As teachers and students adapt to the new normal, Zoom, Google meet, Microsoft teams, or Cisco WebEx have become the most sought-after platforms for distance learning. The challenge for teachers and students in online learning is active peer engagement. To encourage problem-based learning, online platforms allow the creation of breakout rooms. Breakout rooms are private chat rooms where small groups of 3-4 students discuss unique problem statements allocated to them and employ peer learning met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Using BRs and giving learners ample time to discuss and share ideas in small groups disconnected from the main room, theoretically, will positively affect students' self-efficacy to participate in active learning activities. As Naik and Govindu (2022) suggest, giving students opportunities to have informal communication in BRs develops student psychology and social skills.…”
Section: Student Active Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Using BRs and giving learners ample time to discuss and share ideas in small groups disconnected from the main room, theoretically, will positively affect students' self-efficacy to participate in active learning activities. As Naik and Govindu (2022) suggest, giving students opportunities to have informal communication in BRs develops student psychology and social skills.…”
Section: Student Active Learningmentioning
confidence: 99%
“…Besides being easy to use, a feature that attracts teachers and students to using Zoom is its breakout rooms (hereafter "BRs"). It allows its host to split participants into small groups in different rooms so that students would have more significant opportunities for student-student interactions, collaborations, and discussions (Naik & Govindu, 2022). Working in small groups increases students' participation and enhances their learning experiences, leading to better academic performance (Cavinato et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to digital tools and distance education are related to educators having limited experience, knowledge of using digital tools and even a fear that digital education may reduce or remove traditional activities on campus [12]. Although modern technology provides new opportunities to activate students, educators have mainly been delivering traditional teacher-based plenary lectures using screen sharing during COVID-19 pandemic lockdowns [34][35][36]. The challenge of such a pedagogy is the lack of active student interaction.…”
Section: The Pedagogical Approachmentioning
confidence: 99%
“…Although they had the opportunity to raise their digital hand for help, they might have been too shy to actively ask for it from educators. Group dynamics are fundamental for learning outcomes in group work [35], and these students might not have been adequately trained on group processes or those involving persons they did not previously know. A scoping review on learning outcomes from digital learning interventions [32] has suggested that the role of teachers and supervisors is even stronger in distant education.…”
Section: The Pedagogical Approachmentioning
confidence: 99%
“…Inwiefern im virtuelle Raum der digitalen Lehre Interaktion geschaffen werden kann, ist Gegenstand zahlreicher aktueller Beiträge, sei es zur Nutzung von Breakoutrooms (siehe z.B. Abdul Aziz, Ganasan & Mohd Yusoff, 2021;Naik & Govindu, 2022) oder dem Schaffen von digitaler Präsenz(Stanisavljevic & Tremp, 2020) oder dem computergestützten kollaborativen Lernen…”
unclassified